PENGARUH PENERAPAN GREEN ACCOUNTING TERHADAP TINGKAT PROFITABILITAS PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - aliah pratiwi; Nafisah Nurulrahmatiah Nurulrahmatiah; Intisari Haryanti Haryanti; Nurul Huda Huda; Ita Iftitah Iftitah (Jurnal Ilmiah Satyagraha, 2023)
This study aims to determine the effect of the application of Green Accounting on the level of profitability of pharmaceutical companies listed on the BEI. Green accounting emerged as a solution to solve the deadlock of problems that occur between economic actors who carry out activities that have an environmental impact and people who feel the impact of environmental activities. This research was conducted on pharmaceutical companies listed on the Indonesia Stock Exchange using the 2017-2021 annual report. The sample in this study were 9 pharmaceutical companies listed on the IDX. The data used is secondary data obtained from www.idx.co.id. The data analysis method used in this study is the panel regression model. Data processing uses the Smart-PLS version 3.0 application. From this study, it was found that the Environmental Development Index (IBL) or environmental costs had no effect on profitability. Likewise, Environmental Performance (PROPER) also has no effect on profitability.